Recent advances in hydrogels applications for tissue engineering and clinical trials - Leila Rezakhani; Maliheh Gharibshahian; Majid Salehi; Sepehr Zamani; Zahra Abpeikar; Omid Ghaderzadeh; Morteza Alizadeh; Alireza Masoudi; Nariman Rezaei; Danial Cheraghali (Regenerative Therapy)
Hydrogels are biomolecules made of artificial and natural polymers. Their quasi-three-dimensional structure has created unique features. They are very hydrophilic, and in addition to the high inflation rate, they also have excellent water maintenance capacity, biodegradability, biocompatibility, and strong mechanical properties. These properties are used in many tissue engineering applications. All these features have made these scaffolds widely used as attractive structures in the world of tissue engineering and regeneration medicine. In addition to research, scaffolds entered the field of medicine and are expected to play a significant role in the repair of many tissues in the future. This study aims to review the various polymers involved in hydrogel fabrication and their application in the repair of diverse tissues and clinical trials.